2007
DOI: 10.1016/j.cell.2007.03.025
|View full text |Cite
|
Sign up to set email alerts
|

LKB1 and SAD Kinases Define a Pathway Required for the Polarization of Cortical Neurons

Abstract: The polarization of axon and dendrites underlies the ability of neurons to integrate and transmit information in the brain. We show here that the serine/threonine kinase LKB1, previously implicated in the establishment of epithelial polarity and control of cell growth, is required for axon specification during neuronal polarization in the mammalian cerebral cortex. LKB1 polarizing activity requires its association with the pseudokinase Stradalpha and phosphorylation by kinases such as PKA and p90RSK, which tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
553
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 374 publications
(591 citation statements)
references
References 71 publications
30
553
2
Order By: Relevance
“…Moreover, LKB1 L and LKB1 S have comparable responses to ONOO Ϫ /metformin treatment, suggesting that Ser-399 in LKB1 S mimics the functionality of Ser-431/428 in LKB1 L . This rectifies previous, seemingly paradoxical findings (22,26,28,29,35,36) regarding the necessity of the Ser-431/428 site in LKB1 L by establishing that the Ser-399 site plays a compensatory role in LKB1 S .…”
Section: Discussionmentioning
confidence: 38%
See 1 more Smart Citation
“…Moreover, LKB1 L and LKB1 S have comparable responses to ONOO Ϫ /metformin treatment, suggesting that Ser-399 in LKB1 S mimics the functionality of Ser-431/428 in LKB1 L . This rectifies previous, seemingly paradoxical findings (22,26,28,29,35,36) regarding the necessity of the Ser-431/428 site in LKB1 L by establishing that the Ser-399 site plays a compensatory role in LKB1 S .…”
Section: Discussionmentioning
confidence: 38%
“…This implies that alternative pathway(s) is (are) implicated in PKA-induced AMPK activation, which further supports the notion that regulation and activity of LKB1 are context-dependent (34). Other studies (35,36) have suggested an important regulatory role played by post-translational modifications in LKB1. It is probable that LKB1 is differentially phosphorylated by different stimuli in different cell types (25), warranting further investigation of the LKB1 regulatory C-terminal domain.…”
Section: Discussionmentioning
confidence: 99%
“…LKB1 can also regulate the polarization of lung cancer cell lines in association with recruitment of the small GTPase, Cdc42, a known regulator of cell polarity see Etienne-Manneville, 2008). Conditional knockout and in vivo RNAi approaches have shown that Lkb1 controls axon specification in a manner that requires the AMPK-related SAD-A and SAD-B kinases (Barnes et al, 2007;Shelly et al, 2007). RNAi studies also showed that LKB1 is required for neuronal migration and centrosome positioning (Asada et al, 2007).…”
Section: Polarity Controlmentioning
confidence: 99%
“…It has recently been demonstrated that an increase in cAMP levels leads to activation of LKB1, which then activates AMPK. The role of cAMP in axon initiation during neuronal polarisation is to regulate the downstream kinase LKB1 by phosphorylation (Barnes et al, 2007;Shelly et al, 2007), which also co-activates mitochondrial biogenesis through AMPK. Furthermore, TAK1, which is activated by TGFβ signalling and controls axonal growth, co-activates mitochondrial biogenesis through AMPK (White et al, 2008;Xie et al, 2006;Yu et al, 2014).…”
Section: Do Neurons Have a Mechanism To Sense Upcoming Energy Needs?mentioning
confidence: 99%